2019
DOI: 10.15195/v6.a6
|View full text |Cite
|
Sign up to set email alerts
|

The Social Stratification of Environmental and Genetic Influences on Education: New Evidence Using a Register-Based Twin Sample

Abstract: The relative importance of genes and shared environmental influences on stratification outcomes has recently received much attention in the literature. We focus on education and the gene-environmental interplay. Specifically, we investigate whether-as proposed by the Scarr-Rowe hypothesis-genetic influences are more important in advantaged families. We argue that the social stratification of family environments affects children's chances to actualize their genetic potential. We hypothesize that advantaged fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 61 publications
(122 reference statements)
2
42
0
1
Order By: Relevance
“…Concerning the final educational degree attained, Baier and Lang (2019) found a pattern following the Scarr-Rowe interaction hypothesis for the young adults in the oldest birth cohort of twins. Whereas genetic influences were more important for educational attainment of twins in families with higher educated parents, shared environmental influences mattered more if parental education was low.…”
Section: Findings On Educational Outcomesmentioning
confidence: 61%
“…Concerning the final educational degree attained, Baier and Lang (2019) found a pattern following the Scarr-Rowe interaction hypothesis for the young adults in the oldest birth cohort of twins. Whereas genetic influences were more important for educational attainment of twins in families with higher educated parents, shared environmental influences mattered more if parental education was low.…”
Section: Findings On Educational Outcomesmentioning
confidence: 61%
“…Using a modified twin correlation model, they showed that the Scarr-Rowe hypothesis adequately describes the pattern of results in middle-childhood andto some degreein adolescence but not in adulthood in our German twin sample. Concerning the final educational degree attained, Baier and Lang (2019) found a pattern following the Scarr-Rowe hypothesis for the young adults in the oldest birth cohort of twins. Regarding the type of schooling track children attended, Schulz et al (2017) showed influences of parental socioeconomic resources over and above children's as well as parent's cognitive abilities.…”
Section: Recent Major Findingsmentioning
confidence: 55%
“…The heritability estimations for different indicators of school performance provide insights about the role of genes and whether children can express their genetic potential related to education. However, when considering genetic influences relevant for education and its predictors, it is important to take into account that the relative importance of genes can depend on environmental conditions (e.g., Heath et al, 1985;Herd et al, 2019;Guo & Stearns, 2002;Turkheimer et al, 2003;Gottschling et al, 2019;Baier & Lang, 2019).…”
Section: Genetic Influences On Children's School Performancementioning
confidence: 99%
“…Research on IQ and educational outcomes has acknowledged the role of the family and considers parents social standing (e.g., Baier & Lang, 2019;Gottschling et al, 2019;Guo & Stearns, 2002;Turkheimer et al, 2003). This research is inspired by the Scarr-Rowe hypothesis, which states that genes relevant for cognitive ability are more important among advantaged children compared to disadvantaged children (Rowe et al, 1999;Scarr-Salapatek, 1971).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation